Perlindungan Hukum Terhadap Konsumen Di Dalam Membeli Barang Bekas/Barang Second - Ketut Ardika; Muhammad Bagus Firmansyah (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the legal protection of consumers in buying used goods. Consumers are one of the parties involved in the sale - purchase of a product. Goods or objects that are traded are not only newly produced goods, but also used goods. In buying and selling activities, consumers will receive rights and obligations, so it is very important that legal protection for consumers is needed to ensure certainty, benefit and legal justice for consumers.